Assessing Organisations’ Readiness for Technological Changes in Construction Industry - Hashim, Norfashiha; Samsuri, Aina Syafiza; Idris, Nur Hidayah (International Journal of Sustainable Construction Engineering and Technology, 2021)
Of late, the advancements in technology have witnessed a spike in the number of schemes aimed towards enhancing the deployment of technologies in construction-based entities, thereby increasing the demand for technological modifications. This paper intends to scrutinise the keenness of construction entities to identify technological changes within the construction sector. The goals of this research work are to ascertain the degree of willingness for technological alterations, the norms which construction entities should possess regarding the readiness for technological alterations, and the obstacles encountered by construction firms in terms of technological alterations. Ten semi-structured interviews were carried out comprising ten G7 contractors in Selangor and Kuala Lumpur regarding on the implementation and adopting the technological changes within their companies. Based on the observations, most construction firms in Malaysia are fairly prepared to encounter technological fluctuations. Furthermore, the research deliberates many norms which are essential to generate the technological readiness in construction firms along with the obstacles which could impact the organisational inclination for technological changes. This work intends to help construction companies evaluate their degree of readiness and organise themselves for better adoption of technological alterations in their businesses.